Application of mixed distributed software architectures for social-productive projects management in peru - Valenzuela Posadas, Jorge (2017)
FONCODES is the public body in charge of financing and managing the execution of social-productive projects throughout the Peruvian territory. The objective of social-productive projects within the framework of the National Strategy of the Ministry of Development and Social Inclusion is to generate economic opportunities for rural households living in poverty and extreme poverty. The key processes to achieve these national strategic objectives are related to the management of portfolios and projects at all stages. The key information of these processes is that related to budget, expenditure authorizations, accountability, liquidation and financial records since it allows evaluating the efficiency of the obtained management results. There are serious limitations during the transmission of information in real time generating bottlenecks in the respective processes. This paper presents the development and application of mixed distributed software architectures to improve the flow and exchange of key information of social-productive projects in the Peruvian territory. A comparison is made of the developed mixed architectures, the monolithic architecture with SOA services and the microservices architecture as a REST API on Cloud. The mixed distributed software architecture satisfies the need to interoperate legacy systems with a monolithic web application and SOA services however also is required satisfies the need to support high peaks of requests in certain processes where microservices deployed on the Cloud are the best choice. The performance tests results obtained on both architectures are presented, allowing a performance comparison of monolithic architecture and microservice architecture. The paper allow to evaluate at high technical level the benefits and challenges that agencies government can face when implement monolithic web applications and microservices on cloud related to execution perfomance and development team management.